Military diasporas
1 online resource (viii, 407 pages)
Keywords: "Military Diasporas proposes a new research approach to analyse the role of foreign military personnel as composite and partly imagined para-ethnic groups. These groups not only buttressed a state or empire's military might but crucially connected, policed and administered (parts of) realms as a transcultural and transimperial class while representing the polity's universal or at least cosmopolitan aspirations at court or on diplomatic and military missions. Case studies of foreign militaries with a focus on their diasporic elements include the Achaemenid Empire, Ptolemaic Egypt, and the Roman Empire in the ancient world. These are followed by chapters on the Sassanid and Islamic occupation of Egypt, Byzantium, the Latin Aegean (Catalan Company) to Iberian Christian noblemen serving North African Islamic rulers, Mamluks and Italian Stradiots. The volume thus covers a broad band of military diasporic experiences and highlights aspects of their role in the building of state and empire from Antiquity to the late Middle Ages and from Persia via Egypt to the Baltic. With a broad chronological and geographic range, this volume is the ideal resource for upper-level undergraduates, postgraduates, and scholars interested in the history of war and warfare from Antiquity to the sixteenth century"--